Environmental management in chrome mining along the Great Dyke : a case study of Zimasco Operations - Chakupa, Tendai (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc(Geography and Environmental Studies))--University of Stellenbosch, 2011.